Micrometastasis Expressing Insulin Arise in Lung and Spleen at Advanced Stage of Rip1-Tag2 Transgenic Mice - Li, Jiang-chao (Ivyspring International Publisher, 2014)
Rip1-Tag2 mice is one overt pancreatic β-cell tumor model, which is widely used for studying pancreas tumor angiogenesis and tumor development. However, tumor metastasis in Rip1-Tag2 mice had rarely been reported, in this present study, we find some micrometastasis in lung and spleen of the Rip1-Tag2 mice at advanced stage, which is important for uncovering metastasis cell characteristics and exploring how to survive in cancer microenvironment. To study the micrometastasis of Rip1-Tag2 mice in advanced pancreatic cancer, we first observed the pathology process of β cell tumor in Rip1-Tag2 mice through HE staining, then we performed immunohistochemistry with insulin antibody, T-antigen antibodies and C-petide antibody on lung and spleen tissues sections from advanced stage, comparing with background wild-type C57BL/6 mice sections. The results indicated that micrometastasis expressing insulin was found in the Rip1-Tag2 mice lung, and spleen. Further evidences demonstrate pathology structure of lung and spleen are damaged. Interestingly and importantly, the expression of T antigen and insulin antibodies are all decreased in advanced stage of primary β cell tumor, which suggest that the at least partly micrometastasis is derived from the early stage or from advanced stage of β cell tumor then return to undifferentiated state like cancer stem cell. The findings contributed to the study of cancer metastasis and cancer stem cell.